Micro-friction stir lap welding of aluminum and copper: A short review - Chee, Kuang Kok; Sued, Mohammad Kamil; Kia, Wai Liew; Jayazerli, Moumen Mahmood; Perumal, Logah; Samylingam, Lingenthiran; Chin, Chin Ooi (Dr D. Pylarinos, 2025)
This review article examines the recent progress in Micro-Friction Stir Lap Welding (μFSLW) of Al-Cu thin sheets, comparing the differences in tool geometry and processing parameters of macro-scale and micro-scale Friction Stir Lap Welding (FSLW) of Al-Cu plates. The effect of microstructural evolution, intermetallic formation, hardness distribution, mechanical joint strength, and electrical conductivity is discussed in detail. The most common defects in μFSLW, such as voids, tunnel defects, and hook formations, along with their impact on heat input and tool movement, are examined. Additionally, strategies to improve joint quality, including the addition of engineering interlayers (e.g. zinc foil) and nanoparticles (e.g. graphene), are explored as they mitigate brittle IMCs, improve grain structure, and enhance both mechanical and electrical properties. Important research gaps, regarding the effects of tool tilt angles and complex tool profiles on the mechanical and electrical joint properties, are highlighted as the potential benefits of assistive technologies, such as ultrasonic vibration, assistive heating and cooling, and assistive magnetic field. Future work is essential to enhance the μFSLW of Al-Cu, investigating complex tool geometries, and improving process parameters.